Neurocardiac signatures of acute mental stress: a sex-comparative study - Selina C. Wriessnegger; Lena Lorenzer; Kyriaki Kostoglou (Frontiers in Neuroscience)
IntroductionMental stress affects nearly everyone, with individual responses varying greatly. The importance of studying mental stress has increased, particularly during the COVID-19 pandemic. Stress has wide-ranging health impacts, from elevating blood pressure to contributing to depression and neurodegenerative conditions.MethodsThis work aimed to uncover reliable correlates of mental stress using Electroencephalogram (EEG) and Electrocardiogram (ECG) methods, with an additional focus on sex differences. Twenty-five volunteers performed time-constrained mental arithmetic tasks under stress, amplified by workspace noise and negative feedback.ResultsResponse-locked heart rate (HR) data revealed a parasympathetic deceleration at response onset, followed by sympathetic rebound, with deeper HR dips linked to higher stress levels. Men showed earlier, longer-lasting HR decelerations, suggesting a time-based regulation strategy, while women exhibited larger, short-lived HR swings during slower responses, indicating an intensity-based response. Neural responses revealed also sex-specific stress effects: in females, stress modulated frontal theta, beta, and the theta/beta ratio–markers of cognitive control. In males, stress increased gamma and decreased delta power, indicating possibly heightened arousal and reduced motor preparation, respectively. While alpha asymmetry was modulated in both sexes, its behavioral relevance and spatial patterns differed.DiscussionThese findings highlight the need for sex-specific models in neuroadaptive systems and stress-monitoring technologies.